2020
DOI: 10.1111/jspn.12302
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of pediatric clinicians regarding pediatric pain management

Abstract: Background: The professional knowledge and personal attitudes of pediatric clinicians regarding pediatric pain are the most important factors impacting pediatric pain relief care. Few studies have investigated the knowledge and attitudes regarding pediatric pain management of clinicians in Taiwan. Purpose: Research purposes were to evaluate the knowledge and attitudes of pediatric clinicians regarding pain management and to describe the barriers of applying pain management across pediatric and neonatal setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 34 publications
1
20
1
2
Order By: Relevance
“…Participating pediatricians displayed better knowledge of pain assessment than nurses. These results are likely consistent with previous studies in Taiwan [ 13 ]. Most participants’ responses indicated that they were unaware of the importance of pain assessment and unable to recognize pediatric patients’ pain, implying that they may improperly assess pain in ill children ( Table 2 , Q20).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Participating pediatricians displayed better knowledge of pain assessment than nurses. These results are likely consistent with previous studies in Taiwan [ 13 ]. Most participants’ responses indicated that they were unaware of the importance of pain assessment and unable to recognize pediatric patients’ pain, implying that they may improperly assess pain in ill children ( Table 2 , Q20).…”
Section: Discussionsupporting
confidence: 93%
“…A structured questionnaire assessed pediatric clinicians’ knowledge regarding pediatric pain management. The content of the questionnaire was adapted from a previous study [ 13 ] and modified to fit the reality of clinical practice in mainland China [ 5 , 11 ]. The questionnaire included 9 demographic questions, and 31 items evaluating knowledge of pediatric pain management.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, different aspects have been suggested as being associated with the application of PM, for example, the knowledge about pain and misconceptions about the quality of comfort care and pediatric palliative care, 16 the profession, 17 the time of day, 18 and the presence of parents. 1 In previous research, training and sufficient knowledge about neonatal pain assessment were named as important factors when it came to pain assessment and management.…”
Section: Introductionmentioning
confidence: 99%
“…1 In previous research, training and sufficient knowledge about neonatal pain assessment were named as important factors when it came to pain assessment and management. 16,[19][20][21] For example, the study by Carlsen Misic et al 19 demonstrated that 34% of nurses in neonatal units felt insecure and perceived their knowledge as insufficient with regard to using a pain scale correctly. Further, Capolingua and Gill 22 found out that nurses with postgraduate clinical training reported more positive attitudes toward premature infant pain assessment and management.…”
Section: Introductionmentioning
confidence: 99%